Adaptation of Candida albicans to environmental pH induces cell wall remodelling and enhances innate immune recognition. - Sarah L Sherrington; Eleanor Sorsby; Nabeel Mahtey; Pizga Kumwenda; Megan D Lenardon; Ian Brown; Elizabeth R Ballou; Donna M MacCallum; Rebecca A Hall (PLoS Pathogens)
Candida albicans is able to proliferate in environments that vary dramatically in ambient pH, a trait required for colonising niches such as the stomach, vaginal mucosal and the GI tract. Here we show that growth in acidic environments involves cell wall remodelling which results in enhanced chitin and β-glucan exposure at the cell wall periphery. Unmasking of the underlying immuno-stimulatory β-glucan in acidic environments enhanced innate immune recognition of C. albicans by macrophages and neutrophils, and induced a stronger proinflammatory cytokine response, driven through the C-type lectin-like receptor, Dectin-1. This enhanced inflammatory response resulted in significant recruitment of neutrophils in an intraperitoneal model of infection, a hallmark of symptomatic vaginal colonisation. Enhanced chitin exposure resulted from reduced expression of the cell wall chitinase Cht2, via a Bcr1-Rim101 dependent signalling cascade, while increased β-glucan exposure was regulated via a non-canonical signalling pathway. We propose that this "unmasking" of the cell wall may induce non-protective hyper activation of the immune system during growth in acidic niches, and may attribute to symptomatic vaginal infection.